Targeting brain cells with glutathione-modulated nanoliposomes: in vitro and in vivo study - Salem HF; Ahmed SM; Hassaballah AE; Omar MM (Dove Medical Press, 2015)
Heba F Salem,1 Sayed M Ahmed,2 Ashraf E Hassaballah,3 Mahmoud M Omar1,4 1Department of Pharmaceutics and Industrial Pharmacy, Beni-suef University, 2Department of Industrial Pharmacy, Assiut University, 3Department of Clinical Pathology, Faculty of Medicine, Assiut University, Assuit, 4Department of Pharmaceutics and Industrial Pharmacy, Deraya University, Egypt Background: The blood–brain barrier prevents many drug moieties from reaching the central nervous system. Therefore, glutathione-modulated nanoliposomes have been engineered to enhance the targeting of flucytosine to the brain. Methods: Glutathione-modulated nanoliposomes were prepared by thin-film hydration technique and evaluated in the primary brain cells of rats. Lecithin, cholesterol, and span 65 were mixed at 1:1:1 molar ratio. The molar percentage of PEGylated glutathione varied from 0 mol% to 0.75 mol%. The cellular binding and the uptake of the targeted liposomes were both monitored by epifluorescent microscope and flow cytometry techniques. A biodistribution and a pharmacokinetic study of flucytosine and flucytosine-loaded glutathione–modulated liposomes was carried out to evaluate the in vivo brain-targeting efficiency. Results: The size of glutathione-modulated nanoliposomes was <100 nm and the zeta potential was more than -65 mV. The cumulative release reached 70% for certain formulations. The cellular uptake increased as molar percent of glutathione increased to reach the maximum at 0.75 mol%. The uptake of the targeted liposomes by brain cells of the rats was three times greater than that of the nontargeted liposomes. An in vivo study showed that the relative efficiency was 2.632±0.089 and the concentration efficiency was 1.590±0.049, and also, the drug-targeting index was 3.670±0.824. Conclusion: Overall, these results revealed that glutathione-PEGylated nanoliposomes enhance the effective delivery of flucytosine to brain and could become a promising new therapeutic option for the treatment of the brain infections. Keywords: nanoliposomes, glutathione-modulated nanoliposomes, brain-targeting